Selvmordsaktioner - Nielsen, Henrik Skov (K&K - Kultur og Klasse, 2007)
Suicide Missions The article falls into two interconnected parts. In part one a diagnosis of the economization of universities and the theoretical developments in the humanities in Denmark is provided with an emphasis on literary theory. Positions and persons associated with literary theory have become so weak and diffuse that theory no longer poses a counter-logic or counter-language to other logics and languages such as political or economical ones, it is claimed. In the second part a predominantly formal analysis of the literary work »The Suicide Mission« (Selvmordsaktionen) is carried out with a wish to show that what the book tells us about democracy, Iraq, state of exception etc. can hardly be understood if one jumps to looking only at the world instead of also in the work.